High Glucose with Insulin Induces Cell Cycle Progression and Activation of Oncogenic Signaling of Bladder Epithelial Cells Cotreated with Metformin and Pioglitazone - Daejin Kim; Byul-Nim Ahn; YeongSeok Kim; Dae Young Hur; Jae Wook Yang; Ga Bin Park; Jung Eun Jang; Eun Ju Lee; Min Jeong Kwon; Tae Nyun Kim; Mi Kyung Kim; Jeong Hyun Park; et al. (Journal of Diabetes Research, 2019)
Metformin and pioglitazone are two commonly prescribed oral hypoglycemic agents for diabetes. Recent evidence suggests that these drugs may contribute to bladder cancer. This study investigated molecular mechanism underlying effects of metformin and pioglitazone in bladder epithelial carcinogenesis in type 2 diabetes. The cells derived from human bladder epithelial cells (HBlEpCs) were treated with metformin or pioglitazone with high glucose and insulin. Cell viability and proliferation were evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and a bromodeoxyuridine incorporation assay, respectively, while cell cycle regulatory factors and oncogene expression were analyzed using western blotting. Metformin or pioglitazone suppressed cell viability concentration and time dependently, which was reversed by exposure to high glucose with or without insulin. Prolonged exposure to high glucose and insulin enhanced cyclin D, cyclin-dependent kinase 4 (Cdk4), and Cdk2 expression and suppressed cyclin-dependent kinase inhibitors p21 and p15/16 in HBlEpC cotreated with pioglitazone and metformin. Levels of tumor suppressor proteins p53 and cav-1 were downregulated while those of the oncogenic protein as c-Myc were upregulated under high glucose and insulin supplementation in HBlEpC cotreated with pioglitazone and metformin. Prolonged exposure to high glucose with or without insulin downregulated B cell lymphoma 2-associated X (Bax) and failed to enhance the expression of extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (p38MAPK) in drug-treated cells. These results suggest that hyperglycemic and insulinemic conditions promote cell cycle progression and oncogenic signaling in drug-treated bladder epithelial cells and uncontrolled hyperglycemia and hyperinsulinemia are probably greater cancer risk factors than diabetes drugs.